Enhancing Legal Safeguards in Bankruptcy: The Role of Exceptio Non Adimpleti Contractus in Balancing Creditor-Debtor Relations - Triana, Yeni; Putra, Tri Anggara; Yusuf, M. Fadly Daeng (Journal of Ecohumanism, 2025)
This study examines the application of the principle of exceptio non adimpleti contractus as a legal safeguard for debtors in bankruptcy cases, addressing the increasing tendency of Indonesian bankruptcy law to favor creditors. Using a normative legal research method, the study analyzes legislation, case law, and judicial decisions to explore how this principle can prevent unjust declarations of bankruptcy. The findings highlight the potential of exceptio non adimpleti contractus to recalibrate the creditor-debtor dynamic, ensuring equitable treatment and fostering a more balanced legal framework. These insights are particularly relevant in the context of modern legal systems adapting to economic complexities, offering both theoretical contributions and practical implications.